PERANCANGAN ULANG RUANG FILING BERDASARKAN ILMU ERGONOMI DI RUMAH SAKIT PANTI RINI KALASAN - Rahmi Primagusti Suardi; Savitri Citra Budi (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2013)
ABSTRACKManagement of medical records file storage in Panti Rini Hospital Kalasan irregular, causing difficulty in the search. From the interview at the time that the information obtained preliminary study Panti Rini Hospital Kalasan plan combines two active file storage space. From the above considerations the designer plans to redesign the effective storage space, comfortable, safe, healthy, and efficient based on the principles of ergonomics in Panti Rini Hospital Kalasan both for officers and file.The theme used in this design is the design of the interior space science filing related to ergonomics are good and true. The idea of re-designing the interior design of the space to suit filing ergomoni science, in order to create space filing a healthy, safe, and convenient for users. Design phase consists of: 1) identification, 2) Pre-design, and 3) design.Pre-Design Phase: The storage space on the active medical record file Panti Rini Hospital Kalasan divided into 2 with a room size measuring 7.5 m x 2.9 m, while the B measuring 4m x 1,4 m. A room there are 6 open shelves, 6 lights and 5 lights on the side, this room has only one entrance and exit vents 5 small corner of the room as a place of entry of the light, and there is no Air Conditioning (AC) and the fan in this room. Space B there are 2 open shelves, 2 lights on, 7 small vents, and 2 window and found no air conditioning or fan. The design phase consists of: 1) Calculate the amount of shelving needs for 5 years showed 10 racks. 2) Determine the appropriate shelf generated based upon the principles of ergonomics open shelving with metal shelves specification of Brother Metal Model B-902 which is modified into a metal rack 2 face models. This model has a metal rack 180 cm tall, the average height of Indonesia has a range of 150 cm and 30 cm hand up so if you want to take a file that does not need to top up the stairs, and it reduces the risk of accidents on the medical records clerk. Their respective shaft height is 36 cm, is adapted to the shape of the existing medical record file at Panti Rini Hospital Kalasan measuring 30 cm long and 22 cm high.Keywords: redesign, storage space, design, storage racks, file medical records